-4w(w+2)(w-1)=0

Simple and best practice solution for -4w(w+2)(w-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4w(w+2)(w-1)=0 equation:


Simplifying
-4w(w + 2)(w + -1) = 0

Reorder the terms:
-4w(2 + w)(w + -1) = 0

Reorder the terms:
-4w(2 + w)(-1 + w) = 0

Multiply (2 + w) * (-1 + w)
-4w(2(-1 + w) + w(-1 + w)) = 0
-4w((-1 * 2 + w * 2) + w(-1 + w)) = 0
-4w((-2 + 2w) + w(-1 + w)) = 0
-4w(-2 + 2w + (-1 * w + w * w)) = 0
-4w(-2 + 2w + (-1w + w2)) = 0

Combine like terms: 2w + -1w = 1w
-4w(-2 + 1w + w2) = 0
(-2 * -4w + 1w * -4w + w2 * -4w) = 0
(8w + -4w2 + -4w3) = 0

Solving
8w + -4w2 + -4w3 = 0

Solving for variable 'w'.

Factor out the Greatest Common Factor (GCF), '4w'.
4w(2 + -1w + -1w2) = 0

Factor a trinomial.
4w((1 + -1w)(2 + w)) = 0

Ignore the factor 4.

Subproblem 1

Set the factor 'w' equal to zero and attempt to solve: Simplifying w = 0 Solving w = 0 Move all terms containing w to the left, all other terms to the right. Simplifying w = 0

Subproblem 2

Set the factor '(1 + -1w)' equal to zero and attempt to solve: Simplifying 1 + -1w = 0 Solving 1 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1w = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1w = 0 + -1 -1w = 0 + -1 Combine like terms: 0 + -1 = -1 -1w = -1 Divide each side by '-1'. w = 1 Simplifying w = 1

Subproblem 3

Set the factor '(2 + w)' equal to zero and attempt to solve: Simplifying 2 + w = 0 Solving 2 + w = 0 Move all terms containing w to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + w = 0 + -2 Combine like terms: 2 + -2 = 0 0 + w = 0 + -2 w = 0 + -2 Combine like terms: 0 + -2 = -2 w = -2 Simplifying w = -2

Solution

w = {0, 1, -2}

See similar equations:

| 5e=100 | | 9/4=x/8 | | (2y+5)(9+y)=0 | | t+t+4t=12 | | 7z-12+18z+8=4-4(5-6z+z) | | 10y-8y-y=16 | | 4-2(x-4)=-3(4x-4) | | 6v-7(1+4v)=-183 | | 10b-10b+2b+b-b=16 | | x^3-x^2y-xy+y^2=0 | | 5y-2y+2y-2y=18 | | 94.6=32.6-T | | 2x/3=-14 | | 16c-13c=15 | | 8m-2m=18 | | -2x-y+2z=1 | | 8a-7a=9 | | Ln(sqrt)x+8=1 | | -x-y+2z=1 | | x+2y-2z=5 | | 14g+6g=20 | | 2a-6b-c=1 | | 17+5z=7 | | 3a+5b+c=-4 | | 10w-8w=8 | | a+3b-2c=7 | | -9.3=B-3.4 | | x^3-x^2y-4x+y^3+xy^2-4y=0 | | y-2z=-2 | | 13d-5d=16 | | -35=5y+5 | | x-y+3z=30 |

Equations solver categories